The Concept of Strategic Partnership as an Input in the Modern Alliance Theory - Czechowska, Lucyna (The Copernicus Journal of Political Studies, 2018)
The article is devoted to a new institution of the international political relations – the strategic partnership. The author analysis the realities of the foreign policy conducted in the first decade of the 21st century and takes a side in the discussion between the neoliberals and the neorealists on the states’ natural tendency to rivalry or cooperation. Settling her concept in the framework of the realists theory of alliances, the author describes the condition of research on the issue and differentiates between the sensu stricte and sensu largo alliance, moving closer the wider understanding of the term. The core of the essay, though, is the presentation of a perfect model of the researched institution. Therefore, the author presents and justifies her own definition and sets constitutive features of the material strategic partnership. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760